Markers of early renal changes induced by industrial pollutants. III. Application to workers exposed to cadmium. Issue 1 (January 1993) - Roels, H; Bernard, A M; Cárdenas, A; Buchet, J P; Lauwerys, R R; Hotter, G; Ramis, I; Mutti, A; Franchini, I; Bundschuh, I
Abstract : Cadmium (Cd) was the third heavy metal investigated in the European collaborative research project on the development and validation of new markers of nephrotoxicity. Fifty workers exposed to Cd and 50 control workers were examined. After application of selection criteria 37 workers (mean age 43) exposed to Cd for an average of 11.3 years; and 43 age matched referents were retained for final analysis. The average concentrations of Cd in blood (Cd-B) and urine (Cd-U) of exposed workers were 5.5 micrograms Cd/l and 5.4 micrograms Cd/g creatinine respectively. By contrast with lead and mercury, Cd had a broad spectrum of effects on the kidney, producing significant alterations in amounts of almost all potential indicators of nephrotoxicity that were measured in urine–namely, low and high molecular weight proteins, kidney derived antigens or enzymes, prostanoids, and various other biochemical indices such as glycosaminoglycans and sialic acid. An increase in beta 2-microglobulin and a decrease of sialic acid concentration were found in serum. Dose-effect/response relations could be established between most of these markers and Cd-U or Cd-B. The thresholds of Cd-U associated with a significantly higher probability of change in these indicators were estimated by logistic regression analysis. Three main groups of thresholds could be identified: one around 2 micrograms Cd/g creatinine mainly associated with biochemical alterations, a second around 4 micrograms Cd/g creatinine for high molecular weight proteins and some tubular antigens or enzymes, and a third one around 10 micrograms Cd/g creatinine for low molecular weight proteins and other indicators. The recent recommendation by the American Conference of Governmental Industrial Hygienists (ACGIH) of 5 micrograms Cd/g creatinine in urine as the biological exposure limit for occupational exposure to Cd appears thus justified, although for most of the effects occurring around this threshold the link with the subsequent development of overt Cd nephropathy is not established. In that respect, the very early interference with production of some prostanoids (threshold 2 micrograms Cd/g creatinine) deserves further investigation; although this effect might contribute to protect the filtration capacity of the kidneys, it might also play a part in the toxicity of Cd on bone.